ANALISIS TINDAK TUTUR TOKOH DAN PENOKOHAN PADA NOVEL TERIMA KASIH CINTA KARYA ADI RUSTANDI SERTA RELEVANSINYA SEBAGAI BAHAN AJAR DI SMA - Rida Anisa; Panca Pertiwi Hidayati; Adi Rustandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study has a goal, namely to find the speech acts contained in the novel Terima Kasih Cinta by Adi Rustandi by analyzing and utilizing the results of the analysis in the novel to be used as alternative teaching materials for class XII in high school. Based on the results of the analysis, it shows locutionary speech acts, illocutionary speech acts, and perlocutionary speech acts. Illocutionary speech acts contain assertive, expressive, directive, commissive, and declarative meanings. Meanwhile, perlocutionary speech acts contain verbal, nonverbal, and verbal nonverbal perlocutionary speech acts. The number of speech acts contained in the novel Terima Kasih Cinta by Adi Rustandi, namely locutionary speech acts in the use of diction, saying is 8, reminding is 1, explaining is 1, stating is 2, telling is 1, calling is 1, and asking is 2. Illocutionary speech contains expressive meanings totaling 2, assertive amounting to7, directive totaling 4, commissive totaling 2, and declarative totaling 1. While perlocutionary speech acts containing verbal perlocutionary speech acts totaling 6, nonverbal amounting to 4, and verbal nonverbal amounting to 5. seen its relevance to the demands of the curriculum, namely on KI and KD.